Interleukin-26 expression in tuberculosis disease and its regulatory effect in macrophage polarization and intracellular elimination of Mycobacterium tuberculosis - Huang, Kaisong; Zhou, Haijin; Chen, Mei; Chen, Rui; Wang, Xiaoping; Chen, Qi; Shi, Zhiyun; Liang, Yanfang; Yu, Luxin; Ouyang, Ping; Li, Li; Jiang, Dan; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Tuberculosis(TB), an infectious disease caused by Mycobacterium tuberculosis (Mtb) infections, remains the leading cause of mortality from a single infectious agent globally. The progression of tuberculosis disease is contingent upon the complex interplay between the host’s immune system and the pathogen Mtb. Interleukin-26 (IL-26), the most recently identified cytokine belonging to the IL-10 family, exhibits both extracellular antimicrobial properties and pro-inflammatory functions. However, the precise role of IL-26 in the host immune defense against Mtb infections and intracellular killing remains largely unexplored. In this study, we observed significantly elevated IL-26 mRNA expression in peripheral blood mononuclear cells of active-TB patients compared to healthy individuals. Conversely, circulating IL-26 levels in the plasma of adult TB patients were markedly lower than those of healthy cohorts. We purified recombinant IL-26 from an E. coli expression system using the Ni-NTA resin. Upon stimulations with the recombinant IL-26, human THP1 cells exhibited rapid morphological changes characterized by increased irregular spindle shape and formation of granular structures. Treating THP1 cells with IL-26 can also lead to heightened expressions of CD80, TNF-α, and iNOS but not CD206 and Arg1 in these cells, indicating an M1 macrophage differentiation phenotype. Furthermore, our investigations revealed a dose-dependent escalation of reactive oxygen species production, decreased mitochondrial membrane potential, and enhanced autophagy flux activity in THP1 macrophages following IL-26 treatment. Moreover, our results demonstrated that IL-26 contributed to the elimination of intracellular Mycobacterium tuberculosis via orchestrated ROS production. In conclusion, our findings elucidated the role of IL-26 in the development of tuberculosis and its contributions to intracellular bacilli killing by macrophages through the induction of M1-polarization and ROS production. These insights may have significant implications for understanding the pathogenesis of tuberculosis and developing novel therapeutic strategies.